2016
DOI: 10.5507/bp.2015.065
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of selected antidepressants and antipsychotics in clinical samples using chromatographic methods combined with mass spectrometry: A review (2006-2015)

Abstract: This review describes major advances and drawbacks in the field of chromatography coupled with single or tandem mass spectrometry (LC-MS, LC-MS/MS and GC/MS) of selected antidepressants (agomelatine, vilazodone) and antipsychotics (iloperidone, asenapine, amisulpride, aripiprazole, melperone, zotepine, ziprasidone). The high specificity in combination with high sensitivity makes these techniques an attractive complementary method to traditional procedures used in routine practice for TDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 100 publications
0
14
0
Order By: Relevance
“…These three SGAPs are among the most efficacious ones and their TDMs are among the better studied. In a recent review, Sistik et al () reported that many analytical techniques have been used for SGAP TDM, but more recently LC‐MS/MS has emerged as the technique of choice. On the other hand, they emphasized that sample preparation is not a completely resolved issue.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…These three SGAPs are among the most efficacious ones and their TDMs are among the better studied. In a recent review, Sistik et al () reported that many analytical techniques have been used for SGAP TDM, but more recently LC‐MS/MS has emerged as the technique of choice. On the other hand, they emphasized that sample preparation is not a completely resolved issue.…”
Section: Resultsmentioning
confidence: 67%
“…These three SGAPs are among the most efficacious ones and their TDMs are among the better studied. In a recent review, Sistik et al (2016) reported that many analytical techniques have been used for SGAP (Mandrioli et al, 2011;Saracino et al, 2010) and three to measure olanzapine (Gopinath et al, 2012;Proença et al, 2013;Sivsivadze et al, 2017), we found no article using SPE for an analytic system measuring more than one of these antipsychotics. Moreover, by using a better sample preparation with two methods of causing protein precipitation at the time of sample preparation (Section 2.3) and during the online SPE (Section 2.4),…”
Section: Contribution To the Literaturementioning
confidence: 74%
“…Mental health issues, including depression and mood disorders, have become far more frequent in recent decades than in the past. 15 The rapid development of new antidepressants with minimal side effects is a desirable effort. In fact, new generations of antidepressants with improved side effect profiles, such as ARP, are becoming increasingly available for the treatment of emotional disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, new generations of antidepressants with improved side effect profiles, such as ARP, are becoming increasingly available for the treatment of emotional disorders. 4 , 15 …”
Section: Discussionmentioning
confidence: 99%
“…Although majority of these methodologies are sufficiently accurate and precise, the intricate pretreatment processes (e.g. extraction and evaporation) and long chromatographic separation times make them less favorable for routine TDM application (Sistik et al, ). For improvements, recently, ultra‐high‐performance liquid chromatography–tandem mass spectrometry (UPLC‐MS/MS) has attracted attention (Patteet et al, ).…”
Section: Introductionmentioning
confidence: 99%